Evaluating sodium-ion pouch cell battery for renewable energy storage under extreme conditions - Shelke, Mehul; Boyer, Jamee M.; Mirzapure, Vinay; Pol, Vilas G. (Communications Chemistry, 2025)
A sodium-ion battery (SIB) is a sustainable energy storage technology based on abundantly available raw materials. It is a commercially viable option because of the processing similarity with Li-ion battery. Most of the energy storage studies focus on the near room temperature performance of different battery chemistries. Herein, we report the ultralow temperature performance of the SIB pouch cell. The cells fabricated using low-temperature compatible components showed significant specific energy values around 96, 74, and 46 Wh kg-1 at room temperature, -25 degrees C, and -50 degrees C, respectively. We demonstrated the battery performance under laboratory conditions as well as under actual windy and snowy environments. Such an exhibition highlights the use case of the SIB pouch cell as an emergency energy storage device in extreme weather conditions. Moreover, charging of SIB cell at -100 degrees C using polycrystalline Si solar cell is also reported, indicating the possibility of deployment for space expeditions.